THE EFFECT OF RATIO OF GAS MIXTURE FOR MECHANICAL PROPERTIES AND CRYSTAL STRUCTURES ON 316L STAINLESS STEEL BIOMATERIAL USING DC SPUTTERING TECHNIQUE - Wiwien Andriyanti; Bunyamin Arsyad; Ravendianto Ravendianto; Tjipto Sujitno; Suprapto Suprapto; Dwi Priantoro (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2019)
316L stainless steel is widely used as an orthopedic implant due to its high corrosion resistance and biocompatibility, but the weakness of these materials is low hardness and high wear. The surface must be modified to improve the material. For the purpose, a titanium nitride (TiN) thin film was deposited on the surface of SS 316L using DC sputtering technique. The sputtering process was carried out for various of a gas mixture of argon (Ar) and nitrogen (N2) such as 90 Ar: 10N2, 80 Ar: 20 N2, 70 Ar: N2, and 60 Ar: 40 N2, while the other parameters kept constant. The objective of the gas mixture variation is to find out the optimum condition of ratio Ar: N2 gas mixture with the highest hardness and lowest wear resistance. From experiment done it’s found that the highest hardness in order of 232.02 VHN, while before being coated the hardness is 133.61 VHN, or there is an increasing hardness by factor 1.73, while the wear resistance reduces from 11.6 × 10-8 mm2/kg to 1.17 × 10-8 mm2/kg or there is reducing in wear resistance by factor 9.9. The optimum conditions were achieved at Ar: N2 ratio = 70:30. From XRD analysis, it can be concluded that the crystal structure of TiN thin film is cubic with the peaks (111), (200), (202), (311) and (222). From cross-section microstructure analysis using Scanning Microscope Electron (SEM), it’s found the thickness of the thin film is 744 nm.